2002
DOI: 10.1111/j.1654-1103.2002.tb02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Ellenberg indicator values judged from physico‐chemical field measurements

Abstract: Abstract. The relationship between mean Ellenberg indicator values (IV) per vegetation relevé and environmental parameters measured in the field usually shows a large variation. We tested the hypothesis that this variation is caused by bias dependent on the phytosociological class. For this purpose we collected data containing vegetation relevés and measured soil pH (3631 records) or mean spring groundwater level (MSL, 1600 records). The relevés were assigned to vegetation types by an automated procedure. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 13 publications
2
119
0
5
Order By: Relevance
“…In practice, the indicator values of Ellenberg's implicitly defined scale seem to work well, but this type of environmental calibration does not include the interaction effect of other factors (Ter Braak and Gremmen, 1987) and could significantly differ from real site conditions. For example, for Vaccinio-Piceetea, Wamelink et al (2002) found a negative relationship between Ellenberg's R values and soil acidity while a positive relationship was expected. Comparison of individual species response and mean sample indicator values can therefore yield inconsistent results.…”
Section: Vegetation Changesmentioning
confidence: 99%
“…In practice, the indicator values of Ellenberg's implicitly defined scale seem to work well, but this type of environmental calibration does not include the interaction effect of other factors (Ter Braak and Gremmen, 1987) and could significantly differ from real site conditions. For example, for Vaccinio-Piceetea, Wamelink et al (2002) found a negative relationship between Ellenberg's R values and soil acidity while a positive relationship was expected. Comparison of individual species response and mean sample indicator values can therefore yield inconsistent results.…”
Section: Vegetation Changesmentioning
confidence: 99%
“…Both floristic and vegetation databases can be used and/or combined using the system of ecological indicators. Wamelink et al [57] suggest, however, that Ellenberg indicator values should not be combined between various vegetation types. The aforementioned combination of vegetation and floristic databases on the basis of ecological indicators should therefore be treated with care.…”
Section: Discussionmentioning
confidence: 99%
“…by using inverse regression (Birks et al 1990). Wamelink et al (2002) and Schaffers & Sýkora (2000) showed that expert systems may lead to biased results, which can be improved by calibrating indicator values with field measurements (e.g., Wamelink et al 2005). Therefore, various statistical calibration techniques were introduced to build such indicator systems (e.g., ter Braak & Barendregt 1986;Huisman et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Ellenberg's indicator values (EIV) have been exhaustively discussed by many authors (e.g., Mucina 1985;Jurko 1986;Klimeš 1987; and recently by Schaffers & Sýkora 2000; Wamelink et al 2002Wamelink et al , 2005, and several aspects of their usage have been criticised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation